2014
DOI: 10.1097/01.dss.0000452625.01889.c3
|View full text |Cite
|
Sign up to set email alerts
|

Objective Evaluation of the Clinical Efficacy of Fractional Radiofrequency Treatment for Acne Scars and Enlarged Pores in Asian Skin

Abstract: Fractional bipolar RF provides clinical efficacy with safety in acne scars and enlarged pores through dermal matrix remodeling combined with tolerable epidermal ablation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 23 publications
1
46
0
3
Order By: Relevance
“…1 Previously, the histological changes produced by the same bipolar FRF devices have been examined in biopsy examinations of acne scar skin tissue. 15,20,21 Omi et al reported remodeling of the dermis to replace acne scar-associated morphological and ultrastructural irregularities with a more normal architecture, particularly in the case of elastic fibers and over-deposition of elastin. 20 Kim et al 15 discovered increases in the levels of procollagen types I and III, as well as elastin.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1 Previously, the histological changes produced by the same bipolar FRF devices have been examined in biopsy examinations of acne scar skin tissue. 15,20,21 Omi et al reported remodeling of the dermis to replace acne scar-associated morphological and ultrastructural irregularities with a more normal architecture, particularly in the case of elastic fibers and over-deposition of elastin. 20 Kim et al 15 discovered increases in the levels of procollagen types I and III, as well as elastin.…”
Section: Discussionmentioning
confidence: 99%
“…15,20,21 Omi et al reported remodeling of the dermis to replace acne scar-associated morphological and ultrastructural irregularities with a more normal architecture, particularly in the case of elastic fibers and over-deposition of elastin. 20 Kim et al 15 discovered increases in the levels of procollagen types I and III, as well as elastin. In addition, in our previous study of atrophic acne scars we observed the thermal denaturation of peri-hair follicle collagen, hair follicles and sebaceous glands.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…28 Fractional bipolar RF provides clinical efficacy with safety for treatment of acne scars and enlarged pores through dermal matrix remodeling combined with tolerable epidermal ablation. 29 Intense pulsed light, combined with intensified pulsed optical and bipolar RF devices also seem to be effective for reducing pores and skin rejuvenation with minimal risk (Table 1). 30,31 The SL structure of enlarged pores bears similarity to the characteristic structures of acne scars, as reported by Kligman 37 ; therefore, various treatments for acne scars could be applied in treating enlarged pores.…”
Section: Botulinum Toxinmentioning
confidence: 99%
“…26.8), scar treatment, and pore size reduction. 16,17,18,19 the noninsulated distal tip delivers RF current. Usually it employs bipolar needles and the electric current runs between the needles.…”
Section: Infiltrative Fractional Rfmentioning
confidence: 99%